Exercise specific loading conditions and movements of squats, lunges, goodmornings and deadlifts - Schellenberg, F.; Taylor, W. R.; Lorenzetti, S. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The purpose of this study was to compare the joint kinematics and loading conditions acting on the knee, hip and lumbar spine during several strength exercises; Squats, Split Squats, Deadlifts and Goodmornings. Kinematic and kinetic data were recorded using an optoelectronic system and force plates. Maximal range of motion and maximal external joint moment were calculated and examined. Using these findings, specific training programs can be prepared for athletes. Specifically, for prevention and rehabilitation of ACL injury, Goodmornings are preferentially suggested in order to shift the hamstrings-toquadriceps ratio towards the hamstrings.